Resin composition for heat dissipating gap filler
Patent Information
- Application Number
- JP2024113394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-26
- Filing Date
- 2024-07-16
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2042-09-29
AI Technical Summary
【0019】 本発明によれば、放熱性ギャップフィラーが、高温条件下に長時間さらされたり、急激な温度変化を受けたりしても、割れや剥がれの発生を低減することができる放熱性ギャップフィラー用樹脂組成物を提供することができる。
Smart Images

Figure 0007637306000001 
Figure 0007637306000002 
Figure 0007637306000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for a heat dissipating gap filler, a heat dissipating gap filler, and an article. [Background technology]
[0002] In recent years, heat generation from electronic devices such as digital home appliances, lithium-ion secondary batteries, and in-vehicle power modules has been steadily increasing due to their larger capacity and higher functionality. On the other hand, in order to make these electronic devices smaller, lighter, and thinner, the components of these devices are increasingly being replaced from metal to resin. Since resins generally have lower thermal conductivity than metals, it is important to efficiently dissipate heat from the components of the electronic devices in order to prevent the heat from rising.
[0003] Therefore, one method known for efficient heat dissipation is to use fillers or adhesives with high thermal conductivity between components. This type of filler or adhesive is called a gap filler, and is generally a material made of a resin component containing a metal oxide with high thermal conductivity. Because it is liquid, it can be applied to complex shapes, and it has the advantage of being able to be automatically mounted using an application device called a dispenser.
[0004] Conventionally, silicone or polyurethane has been used as the resin component of such gap fillers.
[0005] Silicone may have elastomeric properties suitable for this application, but when used near electrical contacts such as battery cells, the volatile silicone contained in it and the low molecular weight siloxanes generated from it can cause contact failure. In addition, since it is a moisture-curing reaction, water may be added, but the generation of voids due to water leads to a decrease in thermal conductivity. Problems such as volume shrinkage due to the evaporation of volatile silicone, low molecular weight siloxane, and water, and reduced storage stability due to water separation from the liquid before curing have also been pointed out.
[0006] Polyurethane can also exhibit excellent elastomeric properties, but its raw material, isocyanate, not only has toxicity concerns, but also reacts with water to form carbon dioxide voids. Therefore, the curing reaction must be carried out in the absence of water to avoid the formation of voids that hinder thermal conductivity. On the other hand, heat-dissipating gap fillers require high concentrations of inorganic fillers with high surface area (small particle size), but these inorganic fillers inevitably adsorb moisture during normal handling, requiring extensive and therefore expensive drying and handling processes.
[0007] Therefore, various heat dissipating gap fillers using resins other than silicone or polyurethane have been investigated.
[0008] For example, Patent Document 1 describes "a two-component epoxy resin composition for casting, which comprises "a main component including (A) a liquid epoxy resin, (B) an inorganic filler, (C) a phosphate ester wetting and dispersing agent, and (D) a urea compound, and a hardener component including (E) a hardener and (F) a hardener accelerator, wherein the content of the (C) phosphate ester wetting and dispersing agent is 0.1 to 5 parts by mass relative to 100 parts by mass of the (A) liquid epoxy resin, and the ratio of the (C) phosphate ester wetting and dispersing agent to the (D) urea compound ((C) / (D)) is 0.1 / 1 to 1.5 / 1." It also describes that "there is provided a two-component epoxy resin composition for casting, which is resistant to filler settling, and which has excellent mechanical strength while maintaining high thermal conductivity and electrical insulation of the cured product, and an electronic part obtained by casting the epoxy resin composition."
[0009] Patent Document 2 describes a two-part curable composition that cures to form a thermally conductive cured product, the composition comprising: a first part including: (i) at least one polymerizable (meth)acrylate monomer component; (ii) a peroxide curing agent component; (iii) one or more co-curing components selected from the group consisting of primary, secondary, or tertiary amines or compounds containing a -CONHNH- group; (iv) a stabilizing component; and (v) a filler component; and a second part including: (i) at least one polymerizable (meth)acrylate monomer component; (ii) a catalyst component that catalyzes the curing reaction; (iii) the stabilizing component; and (iv) a thermally conductive filler component, at least one part of the composition having a filler component including a thermally conductive filler. Patent Document 2 also describes that the composition described in Patent Document 2 is useful for bonding heat-generating components such as electrical components to a substrate such as a heat sink.
[0010] Furthermore, Patent Document 3 describes a thermally conductive gap filler comprising an aziridino-functional polyether polymer and at least 30 volume % of a thermally conductive filler based on the total volume of the gap filler, and describes that the thermally conductive gap filler of Patent Document 3 may be suitable for use in electronic applications such as battery assemblies.
[0011] Recently published Patent Document 4 describes a curable composition comprising a polyol component including one or more polyols, a functional butadiene component, and a thermally conductive filler present in an amount of at least 20% by weight based on the total weight of the curable composition, the curable composition having a thermal conductivity of at least 0.5 W / (mK) after curing. It is described that the curable composition of Patent Document 4 may be used, for example, as a thermally conductive gap filler, which may be suitable for use in electronic technology applications such as battery assemblies. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2016-60826 A [Patent Document 2] Special Publication No. 2007-528437 [Patent Document 3] Special Publication No. 2020-511732 [Patent Document 4] Special Publication No. 2022-507500 Summary of the Invention [Problem to be solved by the invention]
[0013] However, the epoxy system of Patent Document 1, at least in the examples, requires curing at high temperatures because curing at room temperature takes a long time when the curing agent is an acid anhydride. In addition, many liquid epoxy compounds are generally compounds that are of concern for mutagenicity. The acrylic system of Patent Document 2 cannot be stored at a temperature above the decomposition temperature of the peroxide curing agent, and the curing temperature must be strictly controlled in order to obtain stable performance from the cured product. In addition, many (meth)acrylate compounds are compounds that have skin sensitization, and there are concerns about the safety of workers. In Patent Document 3, there are concerns about toxicity due to the aziridino group, and since it is generally a water-soluble resin, there is a high possibility that it contains a lot of water in the system, leading to the generation of voids and volumetric shrinkage.
[0014] The gap filler of Patent Document 4 can be said to improve the shortcomings of the gap fillers such as the silicone or polyurethane described above, and the epoxy-based, acrylic-based, or aziridino-functional polyether polymers described in Patent Documents 1 to 3. However, when exposed to high temperatures for a long period of time or subjected to a sudden temperature change, the gap filler may crack or peel off.
[0015] Therefore, an object of the present invention is to provide a resin composition for a heat dissipating gap filler, which can reduce the occurrence of cracking or peeling even when the heat dissipating gap filler is exposed to high temperature conditions for a long period of time or is subjected to a sudden temperature change. [Means for solving the problem]
[0016] As a result of intensive research, the present inventors have found that a resin composition for a heat-dissipating gap filler comprising maleic anhydride-modified polybutadiene, a hydroxyl-modified polybutadiene, a thermally conductive filler, and an antioxidant, wherein the content of the antioxidant is 0.01% by mass or more when the total amount of the resin composition for a heat-dissipating gap filler is taken as 100% by mass, and the resin composition for a heat-dissipating gap filler has a thermal conductivity of 1.0 W / m·K or more after curing, can reduce the occurrence of cracking and peeling even when the heat-dissipating gap filler is exposed to high temperature conditions for a long period of time or is subjected to a sudden temperature change, and have completed the present invention.
[0017] That is, according to the present invention, there are provided a resin composition for a heat dissipating gap filler, a heat dissipating gap filler, and an article, as shown below.
[0018] [1] Maleic anhydride modified polybutadiene; Hydroxyl-modified polybutadiene; A thermally conductive filler; Antioxidants, A resin composition for a heat dissipating gap filler comprising: the content of the antioxidant is 0.01% by mass or more when the total amount of the resin composition for heat dissipating gap fillers is taken as 100% by mass, The resin composition for a heat dissipating gap filler has a thermal conductivity of 1.0 W / m·K or more after curing. [2] The resin composition for heat dissipating gap fillers according to [1] above, wherein the content of the thermally conductive filler is 70% by mass or more when the total amount of the resin composition for heat dissipating gap fillers is 100% by mass. [3] The resin composition for a heat dissipating gap filler according to [1] or [2] above, wherein the antioxidant comprises at least one selected from the group consisting of a phenol-based antioxidant and a phosphorus-based antioxidant. [4] The resin composition for a heat dissipating gap filler according to [3] above, wherein the antioxidant comprises a phenol-based antioxidant. [5] The resin composition for a heat dissipating gap filler according to any one of the above [1] to [4], further comprising a curing accelerator. [6] The resin composition for a heat dissipating gap filler according to [5] above, wherein the curing accelerator comprises an amine curing accelerator. [7] The resin composition for a heat dissipating gap filler according to [6] above, wherein the amine curing accelerator has a pKa of 8.0 or more. [8] The resin composition for a heat dissipating gap filler according to any one of the above [1] to [7], which is a two-component type resin composition for a heat dissipating gap filler. [9] A liquid containing the maleic anhydride modified polybutadiene and the thermally conductive filler; The resin composition for a heat dissipating gap filler according to [8] above, further comprising a liquid B containing the hydroxyl group-modified polybutadiene and the thermally conductive filler.
[10] A heat dissipating gap filler obtained by curing the resin composition for a heat dissipating gap filler according to any one of the above [1] to [9].
[11] An article comprising the heat dissipating gap filler according to
[10] above. Effect of the Invention
[0019] According to the present invention, it is possible to provide a resin composition for a heat dissipating gap filler that can reduce the occurrence of cracking or peeling even when the heat dissipating gap filler is exposed to high temperature conditions for a long period of time or is subjected to a sudden temperature change. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment for carrying out the present invention will be described in detail. Note that this embodiment is merely one embodiment for carrying out the present invention, and the present invention is not limited to this embodiment, and various modified embodiments are possible within the scope of the gist of the present invention. Note that "~" between numbers in the text indicates "above" or "below" unless otherwise specified.
[0021] [Resin composition for heat dissipating gap filler] The resin composition for a heat-dissipating gap filler of the present embodiment comprises maleic anhydride-modified polybutadiene, a hydroxyl-modified polybutadiene, a thermally conductive filler, and an antioxidant, wherein the content of the antioxidant is 0.01% by mass or more when the total amount of the resin composition for a heat-dissipating gap filler is taken as 100% by mass, and the thermal conductivity of the resin composition for a heat-dissipating gap filler after curing is 1.0 W / m·K or more.
[0022] The thermal conductivity of the heat dissipating gap filler resin composition of this embodiment after curing is 1.0 W / m·K or more. From the viewpoint of further improving thermal conductivity, the thermal conductivity of the heat dissipating gap filler resin composition of this embodiment after curing is preferably 1.5 W / m·K or more, more preferably 2.3 W / m·K or more, even more preferably 2.5 W / m·K or more, and even more preferably 2.7 W / m·K or more. The upper limit is not particularly limited, and may be, for example, 10.0 W / m·K or less, 8.0 W / m·K or less, or 5.0 W / m·K or less. The thermal conductivity of the heat dissipating gap filler resin composition of this embodiment after curing can be set within the range of this embodiment by adjusting, for example, the type and content of the thermally conductive filler and the types and contents of the maleic anhydride-modified polybutadiene and hydroxyl group-modified polybutadiene. The thermal conductivity of the heat dissipating gap filler resin composition after curing is a value measured by the method described in the examples.
[0023] The Shore OO type hardness of the resin composition for a heat dissipating gap filler of this embodiment, measured in accordance with ASTM D2240, is preferably 80 or less, more preferably 75 or less, and even more preferably 70 or less, from the viewpoint of further reducing the occurrence of cracking and peeling of the heat dissipating gap filler, and the lower limit is not particularly limited, but may be, for example, 40 or more, or 43 or more. In this specification, the hardness refers to the hardness measured on a sample prepared by the method described in the Examples.
[0024] The Shore O hardness of the resin composition for a heat dissipating gap filler of this embodiment, measured in accordance with ASTM D2240, is preferably 50 or less, more preferably 45 or less, and even more preferably 40 or less, from the viewpoint of further reducing the occurrence of cracking and peeling of the heat dissipating gap filler, and the lower limit is not particularly limited, but may be, for example, 10 or more, or 13 or more.
[0025] The resin composition for a heat dissipating gap filler of the present embodiment is preferably a two-part type resin composition for a heat dissipating gap filler. When the resin composition for a heat dissipating gap filler is a two-part type resin composition for a heat dissipating gap filler, the storage stability of the resin composition for a heat dissipating gap filler before curing is further improved. When the resin composition for a heat dissipating gap filler of the present embodiment is a two-component type resin composition for a heat dissipating gap filler, it preferably contains a liquid A containing a maleic anhydride-modified polybutadiene and a thermally conductive filler, and a liquid B containing a hydroxyl-modified polybutadiene and a thermally conductive filler. When the resin composition for heat dissipating gap filler of this embodiment is cured at room temperature, it is preferable that the maleic anhydride-modified polybutadiene and the hydroxyl-modified polybutadiene, which are the resin components, are not mixed during storage but are mixed before use. That is, liquid A containing maleic anhydride-modified polybutadiene and liquid B containing hydroxyl-modified polybutadiene are stored separately, and mixed before use, and then injected or coated, and cured to form a heat dissipating gap filler.
[0026] When the heat dissipating gap filler is a two-component type, from the viewpoint of further improving the supply stability using a pump in an application device when applying the heat dissipating gap filler, the viscosity of Part A is preferably 500 Pa·s or less, more preferably 400 Pa·s or less, even more preferably 300 Pa·s or less, and even more preferably 280 Pa·s or less, and from the viewpoint of further improving the handleability, the viscosity is preferably 10 Pa·s or more, more preferably 20 Pa·s or more, even more preferably 50 Pa·s or more, even more preferably 100 Pa·s or more, and even more preferably 200 Pa·s or more. When the heat dissipative gap filler is a two-component type, from the viewpoint of further improving the supply stability using a pump in an application device when applying the heat dissipative gap filler, the viscosity of component B is preferably 500 Pa·s or less, more preferably 400 Pa·s or less, even more preferably 300 Pa·s or less, and even more preferably 280 Pa·s or less, and from the viewpoint of further improving the handleability, the viscosity is preferably 10 Pa·s or more, more preferably 20 Pa·s or more, even more preferably 50 Pa·s or more, even more preferably 100 Pa·s or more, and even more preferably 200 Pa·s or more. The viscosities of Liquid A and Liquid B in this specification are values measured by the method described in the Examples.
[0027] When the heat dissipating gap filler is a two-component type, from the viewpoint of further improving thermal conductivity, the thermal conductivity of component A is preferably 1.0 W / m·K or more, more preferably 1.5 W / m·K or more, even more preferably 2.0 W / m·K or more, even more preferably 2.5 W / m·K or more, even more preferably 2.7 W / m·K or more, even more preferably 3.0 W / m·K or more, and even more preferably 3.5 W / m·K or more. The upper limit is not particularly limited, and may be, for example, 10.0 W / m·K or less, 8.0 W / m·K or less, or 5.0 W / m·K or less. When the heat dissipating gap filler is a two-component type, from the viewpoint of further improving thermal conductivity, the thermal conductivity of component B is preferably 1.0 W / m·K or more, more preferably 1.5 W / m·K or more, even more preferably 2.0 W / m·K or more, even more preferably 2.5 W / m·K or more, even more preferably 2.7 W / m·K or more, even more preferably 3.0 W / m·K or more, and even more preferably 3.5 W / m·K or more. The upper limit is not particularly limited, and may be, for example, 10.0 W / m·K or less, 8.0 W / m·K or less, or 5.0 W / m·K or less. The thermal conductivity of liquid A and liquid B in this specification is the value measured by the method described in the Examples.
[0028] Each component constituting the resin composition for heat dissipating gap fillers will be described below.
[0029] <Maleic anhydride modified polybutadiene> The maleic anhydride-modified polybutadiene of the present embodiment is produced by modifying a butadiene homopolymer with maleic anhydride, and specific examples thereof include RICON 130MA8, RICON 131MA5, RICOBOND 1731, and RICOBOND 1756 manufactured by Cray Valley, and POLYVEST MA75 manufactured by Evonik.
[0030] When the total amount of the resin composition for a heat dissipating gap filler of the present embodiment is taken as 100 mass%, from the viewpoint of further improving the performance balance between handleability and sheet formability, the content of the maleic anhydride modified polybutadiene of the present embodiment is preferably 0.2 mass% or more, more preferably 0.5 mass% or more, even more preferably 1.0 mass% or more, and even more preferably 1.2 mass% or more, and from the viewpoint of setting the viscosity in a more appropriate range, the content is preferably 10.0 mass% or less, more preferably 7.0 mass% or less, even more preferably 6.0 mass% or less, and even more preferably 5.5 mass% or less.
[0031] When the heat dissipating gap filler is a two-component type, the content of maleic anhydride modified polybutadiene in Part A, when the total amount of Part A is taken as 100% by mass, is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, even more preferably 2.0% by mass or more, and even more preferably 2.4% by mass or more, from the viewpoint of further improving the handleability, and is preferably 20.0% by mass or less, more preferably 14.0% by mass or less, even more preferably 12.0% by mass or less, and even more preferably 11.0% by mass or less, from the viewpoint of setting the viscosity in a more appropriate range.
[0032] <Hydroxyl-modified polybutadiene> The hydroxyl-modified polybutadiene of the present embodiment is obtained by hydroxylating polybutadiene, and specific examples thereof include Poly bd R-20LM from Cray Valley Corporation, Poly bd R-15HT and Poly bd R-45HT from Idemitsu Kosan Co., Ltd., POLYVEST HT from Evonik Corporation, NISSO-PB G-1000, NISSO-PB G-2000 and NISSO-PB G-3000 from Nippon Soda Co., Ltd., and Hydroxyl-terminated Polymer Butadiene from Zibo Corporation.
[0033] The content of the hydroxyl-modified polybutadiene of this embodiment, when the total amount of the resin composition for a heat dissipating gap filler of this embodiment is taken as 100 mass%, from the viewpoint of further improving the handleability, is preferably 0.2 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.4 mass% or more, and even more preferably 0.5 mass% or more, and from the viewpoint of setting the viscosity in a more appropriate range, is preferably 10.0 mass% or less, more preferably 7.0 mass% or less, even more preferably 5.0 mass% or less, even more preferably 3.0 mass% or less, even more preferably 2.0 mass% or less, and even more preferably 1.8 mass% or less.
[0034] When the heat dissipating gap filler is a two-component type, the content of hydroxyl-modified polybutadiene in Part B, when the total amount of Part B is taken as 100% by mass, is preferably 0.5% by mass or more, more preferably 0.7% by mass or more, and more preferably 1.0% by mass or more from the viewpoint of further improving handleability, and is preferably 20.0% by mass or less, more preferably 14.0% by mass or less, even more preferably 10.0% by mass or less, even more preferably 6.0% by mass or less, even more preferably 4.0% by mass or less, and even more preferably 3.6% by mass or less from the viewpoint of setting the viscosity in a more appropriate range.
[0035] The content of the maleic anhydride-modified polybutadiene of this embodiment and the hydroxyl-modified polybutadiene of this embodiment is determined in consideration of the number of maleic anhydride residues of the maleic anhydride-modified polybutadiene involved in the reaction, the number of hydroxyl groups of the hydroxyl-modified polybutadiene, and the physical properties of the resin obtained after the reaction. The total content of the maleic anhydride-modified polybutadiene of this embodiment and the hydroxyl-modified polybutadiene of this embodiment is, for example, 0.01 to 25 mass%, preferably 0.5 to 25 mass%, when the total amount of the resin composition for heat dissipating gap filler of this embodiment is 100 mass%. The total content of the maleic anhydride-modified polybutadiene of this embodiment and the hydroxyl-modified polybutadiene of this embodiment, when the total amount of the resin composition for a heat dissipating gap filler of this embodiment is taken as 100 mass%, from the viewpoint of further improving handleability, is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, even more preferably 1.0 mass% or more, even more preferably 2.0 mass% or more, and even more preferably 3.0 mass% or more, and from the viewpoint of setting the viscosity in a more appropriate range, is preferably 25 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less, and even more preferably 10 mass% or less.
[0036] <Thermal conductive filler> As the thermally conductive filler of this embodiment, any known thermally conductive filler can be used, but when breakthrough voltage is a concern, electrically insulating thermally conductive fillers are preferred.
[0037] Examples of the electrically insulating thermally conductive filler include inorganic particles such as oxides, hydrates, nitrides, carbonates, and carbides, and the oxides preferably include silicon oxide, aluminum oxide, magnesium oxide, zinc oxide, and the like, the hydrates preferably include aluminum hydroxide, magnesium hydroxide, and the like, the nitrides preferably include boron nitride and aluminum nitride, the carbonates preferably include magnesium carbonate and anhydrous magnesium carbonate, and the carbides preferably include silicon carbide. If electrical insulation is not a consideration, graphite, carbon nanotubes, and metals such as aluminum can also be used.
[0038] The thermally conductive filler of the present embodiment preferably contains at least one selected from the group consisting of aluminum oxide, aluminum hydroxide, aluminum nitride, zinc oxide, anhydrous magnesium carbonate, and silicon carbide.
[0039] When the total amount of the resin composition for heat dissipating gap filler of the present embodiment is taken as 100 mass%, from the viewpoint of further improving thermal conductivity, the content of the thermal conductive filler in this embodiment is preferably 70 mass% or more, more preferably 75 mass% or more, even more preferably 80 mass% or more, and even more preferably 85 mass% or more, and from the viewpoint of further improving handleability, it is preferably 99 mass% or less, more preferably 97 mass% or less, and even more preferably 95 mass% or less.
[0040] When the heat dissipating gap filler is a two-component type, the heat conductive filler is preferably contained in both liquid A and liquid B. By containing the heat conductive filler in both liquid A and liquid B, the balance of the viscosities of liquid A and liquid B can be made more appropriate, and the operability when mixing liquid A and liquid B can be further improved. When the heat dissipating gap filler is of a two-component type, the content of the heat conductive filler in Part A, when the total amount of Part A is taken as 100 mass%, is, from the viewpoint of further improving thermal conductivity, preferably 70 mass % or more, more preferably 75 mass % or more, even more preferably 80 mass % or more, and even more preferably 85 mass % or more, and, from the viewpoint of further improving handleability, is preferably 99 mass % or less, more preferably 97 mass % or less, and even more preferably 95 mass % or less. When the heat dissipating gap filler is of a two-component type, the content of the heat conductive filler in component B, when the total amount of component B is taken as 100 mass%, is, from the viewpoint of further improving thermal conductivity, preferably 70 mass % or more, more preferably 75 mass % or more, even more preferably 80 mass % or more, and even more preferably 85 mass % or more, and, from the viewpoint of further improving handleability, is preferably 99 mass % or less, more preferably 97 mass % or less, and even more preferably 95 mass % or less.
[0041] These thermally conductive fillers can be used in combination with one or more types, or with the same type of inorganic particles with different particle sizes, or by adjusting the content, to control the thermal conductivity and the viscosity of the resin composition. However, in order to maximize the thermal conductivity and control the viscosity of the resin composition for heat dissipating gap fillers within a range that allows easy operations such as injection and application, it is preferable to use a combination of inorganic particles with different particle sizes. By doing so, it is possible to further improve the thermal conductivity while adjusting the viscosity to an appropriate level. In addition, when imparting flame retardancy, it is also possible to use hydrates, such as selecting aluminum hydroxide or magnesium hydroxide instead of oxides.
[0042] <Antioxidants> Since the heat dissipating gap filler is intended for heat dissipation, it is naturally used in places where it is exposed to high temperatures for long periods of time or repeatedly exposed to high temperatures and room temperatures. The resin composition for heat dissipating gap filler of this embodiment is susceptible to thermal degradation of the double bonds derived from the butadiene chains due to heat, water, oxygen, etc., as well as crosslinking reactions between the butadiene chains, so that the obtained heat dissipating gap filler becomes hard and brittle, causing cracking and peeling. In order to further reduce this cracking and peeling, the resin composition for heat dissipating gap filler of this embodiment contains an antioxidant. As the antioxidant, any known antioxidant can be used, but it is preferable that the antioxidant contains at least one selected from the group consisting of a phenol-based antioxidant, a phosphorus-based antioxidant, a thiol-based antioxidant, a diphenylamine-based antioxidant, an ascorbic acid-based antioxidant, and a hindered amine-based antioxidant, it is more preferable that the antioxidant contains at least one selected from the group consisting of a phenol-based antioxidant and a phosphorus-based antioxidant, and it is even more preferable that the antioxidant contains a phenol-based antioxidant. As the antioxidant, it is preferable to use one or more primary antioxidants and / or secondary antioxidants.
[0043] The primary antioxidant traps peroxy radicals to prevent the oxidative deterioration of the resin. Any known primary antioxidant can be used as the primary antioxidant, but phenol-based antioxidants are preferred, including hexamethylene bis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 4,4'-thiobis(6-tert-butyl-m-cresol), 2,2'-methylene bis(4-methyl-6-tert-butylphenol), bis[3,3-bis(4-hydroxy-3-tert-butylphenyl)butyric acid]glycol ester, 2,2'-ethylidene bis(4,6-di-tert-butylphenol), 2,2'-ethylidene bis(4-sec-butyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl) Butane, bis[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl]terephthalate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-2,4,6-trimethylbenzene, 1,3,5-tris[(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, 2-tert-butyl-4-methyl-6-(2-acryloyloxy-3-tert-butyl-5-methylbenzyl)phenol, 3,9-bis[1,1-dimethyl-2-{(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,10-tetraoxaspiro[5.5]Undecane, triethylene glycol bis[(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], n-octadecyl-3-(4'-hydroxy-3',5'-di-tert-butylphenyl)butane, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[ 3-(3,5-di-tert-butyl-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)trione, 3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropanoate methyl, benzenepropanoic acid 3,5-bis(1,1-dimethylethyl)-4-hydroxy-C7-C9 side chain alkyl ester, 4,6-bis(octylthiomethyl)-o-cresol, and the like are examples. From the viewpoint of further preventing cracking and peeling of the heat dissipating gap filler and maintaining an appropriate hardness, it is preferable that the phenol-based antioxidant contains at least one selected from the group consisting of 4,4'-thiobis(6-tert-butyl-m-cresol), thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 4,6-bis(octylthiomethyl)-o-cresol.
[0044] Secondary antioxidants decompose hydroxide radicals generated by the oxidation of double bonds, thereby preventing oxidative deterioration of resins. As the secondary antioxidant, a conventionally known secondary antioxidant can be used, but a phosphorus-based antioxidant is preferred, and examples thereof include trisnonylphenyl phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl]phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tri-tert-butylphenyl) (tridecyl) pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4'-n-butylidenebis(2-tert-butyl-5-methylphenol) diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite, tetrakis(2,4-di-tert-butylphenyl)biphenyl Examples include diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)-2-ethylhexyl phosphite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like.
[0045] In order to obtain an antioxidant effect without sacrificing other performances, the content of these antioxidants is, for example, 0.01 to 20 mass %, and preferably 0.4 to 20 mass %, when the total amount of the resin composition for heat dissipating gap fillers of the present embodiment is taken as 100 mass %. The content of the antioxidant is 0.01% by mass or more, when the total amount of the resin composition for a heat dissipating gap filler of this embodiment is taken as 100% by mass, and from the viewpoint of further improving the antioxidant effect, it is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.4% by mass or more, and even more preferably 0.5% by mass or more, and from the viewpoint of further improving the balance between thermal conductivity, handleability, and the like, it is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, even more preferably 10.0% by mass or less, even more preferably 8.0% by mass or less, even more preferably 5.0% by mass or less, even more preferably 3.0% by mass or less, and even more preferably 1.0% by mass or less.
[0046] When the heat dissipating gap filler is of a two-component type, the antioxidant may be contained in only one of the A and B components, or may be contained in both the A and B components. The content of the antioxidant contained in Liquid A, when the total amount of Liquid A is taken as 100% by mass, from the viewpoint of further improving the antioxidant effect, is preferably 0.025% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, and from the viewpoint of further improving the balance between thermal conductivity, handleability, and the like, is preferably 25.0% by mass or less, more preferably 20.0% by mass or less, even more preferably 15.0% by mass or less, even more preferably 10.0% by mass or less, even more preferably 8.0% by mass or less, even more preferably 5.0% by mass or less, even more preferably 3.0% by mass or less, even more preferably 1.5% by mass or less, even more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less. The content of the antioxidant contained in Liquid B, when the total amount of Liquid B is taken as 100% by mass, is preferably 0.025% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, from the viewpoint of further improving the antioxidant effect, and is preferably 25.0% by mass or less, more preferably 20.0% by mass or less, even more preferably 15.0% by mass or less, even more preferably 10.0% by mass or less, even more preferably 8.0% by mass or less, even more preferably 5.0% by mass or less, even more preferably 3.0% by mass or less, even more preferably 1.5% by mass or less, even more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less, from the viewpoint of further improving the balance between thermal conductivity, handleability, and the like.
[0047] <Curing accelerator> From the viewpoint of accelerating the curing reaction, the resin composition for a heat dissipating gap filler of this embodiment preferably further contains a curing accelerator. The curing accelerator is not particularly limited as long as it has the effect of accelerating the curing reaction, but an amine-based curing accelerator is preferred. Among them, the pKa of the amine-based curing accelerator is preferably 8.0 or more, more preferably 9.0 or more, and even more preferably 9.5 or more. Specifically, imidazoles such as 2-ethyl-4-ethylimidazole and 1-cyanoethyl-2-ethyl-4-ethylimidazole, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo(4,3,0)nonene-5 (DBN), hexahydro-1,3,5-tris(3-dimethylaminopropyl)-1,3,5-triamine, 1,5-diazabicyclo(4,3,0)nonene-5 (DBN), ... tertiary amines such as N,N,N',N'',N''-pentamethyldiethylenetriamine, N,N,N',N'-tetramethylhexamethylenediamine, and N-methyldicyclohexylamine; secondary amines such as 4,4'-methylenebis(N-sec-butylcyclohexanamine) and N,N'-di-sec-butyl-p-phenylenediamine; octylate salts of DBU or DBN; and 1,1,3,3-tetramethylguanidine. The content of these curing accelerators is preferably 0.01 to 5% by mass based on the total amount of the resin composition for heat dissipating gap fillers of the present invention, taking into consideration the need to adjust the initial curing time appropriately.
[0048] <Plasticizer> The resin composition for a heat dissipating gap filler of this embodiment preferably further contains a plasticizer from the viewpoint of adjusting the viscosity of the resin. The plasticizer is preferably a liquid at room temperature with a flash point of 200°C or higher so that it remains inside the cured product, and one or more of the liquids can be used as long as they do not inhibit the curing reaction. Examples include esters such as di-2-ethylhexyl phthalate (DOP), diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), di-2-ethylhexyl adipate (DOA), diisononyl adipate (DINA), tri-2-ethylhexyl trimellitate (TOTM), and tricresyl phosphate (TCP), and fatty acid esters modified with animal and vegetable oils.
[0049] The content of the plasticizer in this embodiment, when the total amount of the resin composition for a heat dissipating gap filler in this embodiment is taken as 100 mass %, from the viewpoint of setting the viscosity of the resin in a more appropriate range, is preferably 1 mass % or more, more preferably 2 mass % or more, and even more preferably 3 mass % or more, and from the viewpoint of further improving the balance between thermal conductivity, handleability, and the like, the content is preferably 10 mass % or less, more preferably 9 mass % or less, and even more preferably 8 mass % or less.
[0050] <Dispersant> From the viewpoint of further improving the dispersibility of the thermally conductive filler, the resin composition for a heat dissipating gap filler of the present embodiment preferably further contains a dispersant. The dispersant is not particularly limited as long as it has the effect of improving the wettability with the resin and improving the dispersibility for the purpose of surface modification of the thermally conductive filler, and for example, cationic, anionic, nonionic and amphoteric surfactants can be mentioned, and one or more of them can be used. Specific examples include KP (manufactured by Shin-Etsu Chemical Co., Ltd.), FLOWRENE (manufactured by Kyoeisha Chemical Co., Ltd.), Solsperse (manufactured by Lubrizol Co., Ltd.), EFKA (manufactured by BASF), AJISPER (manufactured by Ajinomoto Fine-Techno Co., Ltd.), Disperbyk and BYK (manufactured by BYK-Chemie Co., Ltd.), Marialim (manufactured by NOF Corp.), and Disparlon (manufactured by Kusumoto Chemical Co., Ltd.). These may be mixed during the production of the A or B liquid, or may be applied to the filler in advance.
[0051] The content of the dispersant in this embodiment, when the total amount of the heat dissipating gap filler resin composition of this embodiment is taken as 100 mass%, from the viewpoint of further improving the dispersibility of the thermally conductive filler, is preferably 0.05 mass% or more, more preferably 0.1 mass% or more, and even more preferably 0.2 mass% or more, and from the viewpoint of further improving the balance between thermal conductivity, handleability, and the like, the content is preferably 1.0 mass% or less, more preferably 0.8 mass% or less, and even more preferably 0.6 mass% or less.
[0052] <Other ingredients> Furthermore, in addition to the additives described above, coupling agents, rheology control agents, defoamers, flame retardants, anti-settling agents, colorants, and the like that are generally blended into compositions of this type may be blended as necessary within the limits that do not impair the effects of the present invention.
[0053] [Method of producing a resin composition for heat dissipating gap filler] The resin composition for a heat dissipating gap filler of this embodiment can be obtained by mixing the various materials using a high-viscosity kneading machine such as a ball mill, a three-roll mill, a kneader, a planetary mixer, or a screw extruder. When the heat dissipating gap filler is a two-component type, components A and B are mixed using a high-viscosity mixer such as a ball mill, a three-roll mill, a kneader, a planetary mixer, or a screw extruder.
[0054] [Method of using the resin composition for heat dissipating gap filler] The resin composition for a heat dissipating gap filler can be used, for example, by injecting the resin composition for a heat dissipating gap filler into a gap between articles, or by applying the resin composition for a heat dissipating gap filler and then bonding the articles together using the applied surface. When the heat dissipating gap filler is a two-part type, for example, parts A and B are mixed in a volume ratio of 1:1 and then injected into the gap between the parts, or applied, and the parts are then bonded together using the applied surface. Of course, it is also possible to mix them by weight, but for this type of work, the method of measuring the volume and mixing is commonly used because it is simple.
[0055] [Heat dissipating gap filler] The heat dissipating gap filler of the present embodiment is obtained by curing the resin composition for heat dissipating gap filler of the present embodiment. The heat dissipating gap filler of the present embodiment may be obtained by at least partially curing the resin composition for heat dissipating gap filler of the present embodiment.
[0056] The heat dissipating gap filler of this embodiment can be obtained, for example, by curing the resin composition for a heat dissipating gap filler of this embodiment at room temperature (for example, 21° C. or higher and 25° C. or lower). When the heat dissipating gap filler is a two-component type, the initial curing time after mixing the A and B components varies depending on the type of curing accelerator, the amount used, and the temperature, but in the present invention, it can be controlled to 5 to 60 minutes at room temperature (for example, 21°C or higher and 25°C or lower), which is considered to be practically preferable, and then it takes about 1 to 3 days to completely cure. In addition, after curing, it has excellent adhesion and moderate flexibility, so it will not peel off or crack for a long period of time even under harsh conditions.
[0057] [Goods] The article of the present embodiment includes the exoergic gap filler of the present embodiment. The articles of this embodiment are electronic devices such as digital home appliances, lithium ion secondary batteries, and in-vehicle power modules. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means "parts by mass".
[0059] Manufacturing Example 1 (Production of A-1 liquid) 2.70 parts of RICON 130MA8 (maleic anhydride modified polybutadiene manufactured by Cray Valley Corporation), 6.00 parts of diisononyl phthalate (plasticizer manufactured by New Japan Chemical Co., Ltd.), 25 parts of B-325 (aluminum hydroxide manufactured by Armolix Corporation), 31 parts of T-60 75MY (aluminum oxide manufactured by Almatis Co., Ltd.), 25 parts of LS-210B (aluminum oxide manufactured by Nippon Light Metal Co., Ltd.), and 10.3 parts of ASFP-20 (aluminum oxide manufactured by Denka Co., Ltd.) were mixed and stirred in a THINKY planetary centrifugal mixer ARE-310 to obtain 100 parts of A-1 liquid.
[0060] Manufacturing Example 2 (Production of B-1 liquid) Poly bd R-20LM (hydroxyl group-modified polybutadiene manufactured by Cray Valley Corporation) 1.05 parts, Lupragen N700 (curing accelerator manufactured by BASF) 0.02 parts, diisononyl phthalate (plasticizer manufactured by New Japan Chemical Co., Ltd.) 6.63 parts, B-325 (aluminum hydroxide manufactured by Armolix Corporation) 25 parts, T-60 75MY (aluminum oxide manufactured by Almatis Co., Ltd.) 31 parts, LS-210B (aluminum oxide manufactured by Nippon Light Metal Co., Ltd.) 25 parts, ASFP-20 (aluminum oxide manufactured by Denka Co., Ltd.) 10.3 parts, and DISPERBYK-145 (dispersant manufactured by BYK-Chemie Co., Ltd.) 1.00 parts were mixed and stirred in a THINKY rotation-revolution type mixer ARE-310 to obtain 100 parts of B-1 liquid.
[0061] According to the formulations in Table 1, solutions A-2 to A-8 were obtained in the same manner as in Production Example 1, and according to the formulations in Tables 2, 3, and 4, solutions B-2 to B-33 were obtained in the same manner as in Production Example 2. The average particle sizes of inorganic particles such as aluminum oxide shown in Tables 1 to 4 are the catalog values of the respective manufacturers.
[0062] [Table 1]
[0063] [Table 2]
[0064] [Table 3]
[0065] [Table 4]
[0066] The eight types of A liquid and 33 types of B liquid obtained were inspected for changes in viscosity and properties after storage at 60°C for one month, and no changes in viscosity or properties exceeding ±20% were observed.
[0067] Example 1: Mixing A-1 and B-3 Liquids and Preparation of Sheets Liquid A-1 and liquid B-3 were filled into 100 ml tanks provided on both sides of a 200 ml Nordson two-liquid parallel cartridge, and the liquids were mixed in a volume ratio of 1:1 by passing them through a 24-stage disposable spiral mixer (static mixer). The obtained mixture was applied to a glass plate and pressed with an aluminum plate equipped with 1 mm-thick spacers on both ends to produce a sheet of 1 mm-thick AB mixture sandwiched between the glass plate and the aluminum plate.
[0068] Using the same procedure as in Example 1, liquid A and liquid B were mixed according to the formulations in Tables 5 and 6 to obtain AB mixed liquids and sheets of Examples 1-24 and Comparative Examples 1-4.
[0069] The AB mixed liquids and sheets obtained in Examples 1 to 24 and Comparative Examples 1 to 4 were subjected to tests (thermal conductivity, hardness, initial curing time, complete curing time, thermal shock test, and aging test) shown in Tables 5 and 6, and the results shown in Tables 5 and 6 were obtained. Furthermore, the A liquid and the B liquid were each subjected to viscosity and thermal conductivity tests, and the results are shown in Tables 1 to 4.
[0070] [Table 5]
[0071] [Table 6]
[0072] "viscosity" The measurements were performed using an Anton Paar rheometer MCR302, PP25 at a measurement temperature of 23°C and a shear rate of 1 (1 / s).
[0073] "Thermal conductivity" Measurements were performed using a TIM tester manufactured by LINSEIS in accordance with ASTM D5470. In Examples 1 to 24 and Comparative Examples 1 to 4, the samples used to measure thermal conductivity were obtained by curing the above-mentioned sheets. The sheets were cured under the following conditions: curing temperature: 25°C, curing time: the complete curing time shown in Tables 5 and 6.
[0074] "hardness" The hardness was measured according to ASTM D2240 using a Shore OO type durometer (manufactured by Teclock Corporation, product name: Teclock Durometer GS-754G) and a Shore O type durometer (manufactured by Teclock Corporation, product name: Teclock Durometer GS-753G). In Examples 1 to 24 and Comparative Examples 1 to 4, the samples for hardness measurement were samples obtained by curing the above-mentioned sheets. The sheets were cured under the conditions of a curing temperature of 25°C and a curing time of complete curing shown in Tables 5 and 6.
[0075] "Initial curing time" The time it took for the viscosity of the AB mixed liquid at 23°C to double from the initial viscosity after mixing was measured.
[0076] "Complete curing time" The AB mixed liquids obtained in the Examples and Comparative Examples were left to stand at 23° C., and the time (number of days) until the hardness became constant was recorded.
[0077] "Thermal shock test" The sheets obtained in the examples and comparative examples were subjected to 2,000 cycles of holding at -40°C for 20 minutes, heating to 100°C in 10 minutes, holding at that temperature for 20 minutes, and cooling to -40°C in 10 minutes (a total of 60 minutes). The degree of cracking and peeling was then evaluated according to the following index. A (very good): No cracks or peeling B (Good): Only cracks or peeling are observed. C (Poor): Both cracks and peeling are observed.
[0078] "Aging test: cracking and peeling" The sheets obtained in the examples and comparative examples were left in an oven at 100° C. for 2000 hours, and then the degree of cracking and peeling was visually observed and evaluated according to the following index. A (very good): No cracks or peeling B (Good): Only cracks or peeling are observed. C (Poor): Both cracks and peeling are observed.
[0079] "Aging Test: Brittleness" <Fragility 1> The hardness after the aging test was measured in the same manner as for "Hardness" above, and brittleness 1 was evaluated according to the following index. It has been confirmed that when the hardness is 85 or more on the Shore OO scale, the material is too hard and tends to break when bent, and when the hardness exceeds 90 on the Shore OO scale or 70 on the Shore O scale, the material is too hard and in most cases breaks when bent. A (very good): Less than 85 at Shore OO B (Good): Shore OO 85 or higher C (Poor): Over 90 on Shore OO or over 70 on Shore O <Fragility 2> In the sheet manufacturing method of the examples and comparative examples, the thickness of the spacer was changed to 3 mm to manufacture a sheet sandwiched with a 3 mm thick AB mixed liquid. The hardness of the sheet sandwiched with a 3 mm thick AB mixed liquid was measured in the same manner as in the above "hardness". During the hardness measurement, the point where the indenter of the hardness meter (indenter shape: hemispherical, tip R1.19 mm) was pierced was observed under an optical microscope at 40 times magnification. Brittleness 2 is an evaluation standard of brittleness based on stricter standards than brittleness 1. Brittleness 2 was evaluated according to the following indexes. A (very good): No cracks on the surface, soft and dented B (Good): There are some cracks on the surface, but the cracks can be repaired by pressing. C (Poor): Cracks are visible on the surface <Overall evaluation of fragility> The brittleness was evaluated according to the following criteria: AA (best): Both Brittleness 1 and Brittleness 2 are rated A A (very good): Brittleness 1 is rated A and Brittleness 2 is rated B BB (Better): Brittleness 1 is rated B and Brittleness 2 is rated B B (Good): Brittleness 1 rated A or B, and Brittleness 2 rated C C (Poor): Brittleness 1 and Brittleness 2 are rated C.
[0080] From the above, the evaluation of cracking / peeling after the thermal shock test and the evaluation of cracking / peeling and brittleness after the aging test in the examples were all better than those in the comparative examples. That is, according to the resin composition for a heat dissipating gap filler of this embodiment, even if the heat dissipating gap filler is exposed to high temperature conditions for a long time or is subjected to a sudden temperature change, the occurrence of cracking and peeling can be reduced. In addition, it is possible to maintain an appropriate hardness under conditions corresponding to actual usage situations. Furthermore, it was found that the two-component heat dissipating gap filler resin composition has good storage stability before mixing of components A and B, and has good room temperature curing properties with an initial curing time of 5 to 60 minutes at room temperature after mixing, making it easy to handle. The resin composition for a heat dissipating gap filler of the present embodiment does not need to contain volatile silicones or low molecular weight siloxanes that cause contact failure, and therefore no voids are generated due to water or gas present in the system or generated during the curing reaction.
[0081] This application claims priority based on Japanese Patent Application No. 2021-163412, filed on October 4, 2021, and Japanese Patent Application No. 2022-072233, filed on April 26, 2022, the disclosures of which are incorporated herein in their entirety.
Claims
1. Maleic anhydride modified polybutadiene; Hydroxyl-modified polybutadiene; A thermally conductive filler; Antioxidants, A resin composition for a heat dissipating gap filler comprising: the content of the antioxidant is 0.05% by mass or more and 20% by mass or less, when the total amount of the resin composition for heat dissipating gap fillers is taken as 100% by mass; The resin composition for a heat dissipating gap filler has a thermal conductivity of 1.0 W / m·K or more after curing.
2. 2. The resin composition for heat dissipating gap fillers according to claim 1, wherein the content of said thermally conductive filler is 70% by mass or more when the total amount of said resin composition for heat dissipating gap fillers is 100% by mass.
3. 3. The resin composition for a heat dissipating gap filler according to claim 1, wherein the antioxidant comprises at least one selected from the group consisting of a phenol-based antioxidant and a phosphorus-based antioxidant.
4. The resin composition for a heat dissipating gap filler according to claim 3 , wherein the antioxidant comprises a phenol-based antioxidant.
5. The resin composition for a heat dissipating gap filler according to claim 1 or 2, further comprising a curing accelerator.
6. The resin composition for a heat dissipating gap filler according to claim 5 , wherein the curing accelerator comprises an amine-based curing accelerator.
7. 7. The resin composition for a heat dissipating gap filler according to claim 6, wherein the amine curing accelerator has a pKa of 8.0 or more.
8. 3. The resin composition for a heat dissipating gap filler according to claim 1, which is a two-component type resin composition for a heat dissipating gap filler.
Citation Information
Patent Citations
Preparation of gap heat conduction material
CN108752628A
THERMALLY CONDUCTIVE TWO-PART ADHESIVE COMPOSITION
JP2007528437A
Epoxy resin composition for two-liquid type casting and electronic component
JP2016060826A
Aziridino-functional polyether thermally conductive gap fillers
JP2020511732A
Curable compositions, articles made therefrom, and methods for making and using same
JP2022507500A